Introduction to logistics systems management - Ghiani, Gianpaolo; Laporte, Gilbert, 1950-; Musmanno, Roberto (Oxford : Wiley-Blackwell, 2013)
Introduction to Logistics Systems Management is the fully revised and enhanced version of the 2004 prize-winning textbook Introduction to Logistics Systems Planning and Control, used in universities around the world. This textbook offers an introduction to the methodological aspects of logistics systems management and is based on the rich experience of the authors in teaching, research and industrial consulting. This new edition puts more emphasis on the organizational context in which logistics systems operate and also covers several new models and techniques tha.
3.6 Case study: Container warehouse location at Hardcastle3.7 Case study: The organ transplantation location-allocation policy of the Italian National Transplant Centre; 3.8 Questions and problems; Chapter 4 Selecting the suppliers; 4.1 Introduction; 4.2 Definition of the set of potential suppliers; 4.3 Definition of the selection criteria; 4.4 Supplier selection; 4.5 Case study: The system for the selection of suppliers at Baxter; 4.6 Questions and problems; Chapter 5 Managing a warehouse; 5.1 Introduction; 5.1.1 Performance parameters; 5.1.2 Decision-making problems; 5.2 Warehouse design.
Includes index.
Keywords: Materials management; Materials handling; Business logistics; BUSINESS & ECONOMICS -- Production & Operations Management; TECHNOLOGY & ENGINEERING -- Industrial Engineering; TECHNOLOGY & ENGINEERING -- Industrial Technology; Business logistics; Materials handling; Materials management; Electronic books